Dampak Diversity Management dan Budaya Organisasi Terhadap Organizational Citizenship Behaviour - Metha Aprilia N.C; Rini Safitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of conducting this study is to analyze and examine the influence of diversity management variables and organizational culture on OCB. Quantitative methods with explanatory research types and multiple linear regression through SPSS 16 software are used by researchers. To obtain data through distributed questionnaires and interviews. Likert scales are used to measure questionnaires. A population of 106 with 84 respondents was used as a sample. A purposive sampling approach is used to sort out samples. The findings of this study are organizational culture to OCB, and diversity management to OCB has a significant effect on each of these independent variables. Also, diversity management and organizational culture to OCB at the Head Office of Perumda Tirta Kanjuruhan Malang have a significant and silmutant influence.